Addressing Long-Term Residual Influences of COVID-19 on Economy and Society for Future Generations: Mothers’ Perceptions of Challenges for Parenting and Children’s Development - Brooklynn Merrifield; Haleh Karimi; Amy Lein; Amy Fairfield (SocioEconomic Challenges)
A healthy workforce is paramount to a thriving society. COVID-19 was a global event that threatened the social and economic well-being of communities around the world. Given the importance of childhood experiences on life outcomes, the increased parental stress and burnout experienced during COVID-19 threatens positive socioeconomic outcomes and future generations' success in the workforce. This mixed-method research employed MaxQDA and JASP software to analyze 201 mothers’ survey responses about their experiences to understand the long-term influences of COVID-19 on future generations entering the workforce. The findings identified significant concerns: mental health, lack of healthy socialization skills, limited access to educational and/or childcare resources, stress and burnout, financial well-being, and lack of access to an extended support network. These concerns influenced mothers' experiences in caring for, supporting, and parenting their children. These also influenced children’s ability to socialize and develop soft skills, which are essential for long-term success both personally and professionally. Findings from the study led to six key recommendations to address the long-term negative impact of COVID-19: developing community support networks, building better access to educational resources, improving flexible work policies, bringing attention to the importance of mental health issues, building leadership and community support programs for parents, and addressing the lack of social skills to prepare the future workforce generation. Addressing these issues will ultimately improve children's development and create a more amenable work-life balance for parents. While often perceived as an individual issue, parental burnout is actually a public health issue. Investing in the development of children today can positively impact the socioeconomic situation for the future of society.